Expression of Stay-Green encoding gene (BoSGR) during postharvest senescence of broccoli - Gómez Lobato, María Eugenia (2014)
Degreening caused by chlorophyll degradation is the most important feature that determines postharvest loss of quality in broccoli. Chlorophyll molecules are assembled to several thylakoid proteins, from which chlorophylls must be released in order to be catabolized. Stay-Green (SGR), a chloroplast-located protein, specifically interacts with light harvesting complex subunits helping toward their destabilization and to the release of chlorophylls. In this work, a fragment of a gene encoding a SGR from broccoli (BoSGR) was cloned. The expression of BoSGR was analyzed and detected an important increment during postharvest senescence, simultaneously with chlorophyll degradation. In order to analyze the effect of different growth regulators, different groups of broccoli heads were treated with cytokinins, ethylene and 1-MCP. Cytokinins and 1-MCP delayed the increment of BoSGR expression whereas ethylene accelerated the process. In addition, several postharvest treatments that delay degreening in broccoli florets were applied to evaluate their effects on BoSGR expression. Samples treated with modified atmosphere, hot air, UV-C or white lights showed a delay in chlorophyll degradation and degreening. In most cases, the treatments also delayed the increment of BoSGR expression during senescence, reaffirming the relationship between the expression of this gene and chlorophyll degradation.